My brilliant life [large type] - Kim, Ae-ran, 1980- (Wheeler Publishing, 2021)
"Areum lives life to its fullest, vicariously through the stories of his parents, conversations with Little Grandpa Jang - his sixty-year-old neighbor and best friend - and through the books he reads to visit the places he would otherwise never see. For several months, Areum has been working on a manuscript, piecing together his parents' often embellished stories about his family and childhood. He hopes to present it on his birthday, as a final gift to his mom and dad; their own falling-in-love story."--Provided by publisher.